Are dental and periapical status related to incidental findings of calcifications along the course of the internal carotid artery in cone-beam computed tomography? - Heraldo Luis Dias Da Silveira; Fernanda Hoffmann Busanello; Carolina Nedel; Mariana Boessio Vizzotto; Spyros Damaskos (Wolters Kluwer Medknow Publications, 2017)
Context: Given that tooth loss, periapical lesion, and manifestations of periodontal disease are generally related to previous inflammatory events and that a linear relationship exists between tooth loss and degree of arterial stiffness, reasonable ground exists to investigate whether there is an association with presence of calcifications along the course of the internal carotid artery (ICA). Aims: This study aims to determine whether an association exists between the extra- and intracranial calcifications of the internal carotid artery (ExCICA and InCICA, respectively) and missing teeth (MT) as well as the periapical index (PAI), in cone-beam computed tomography (CBCT) scans. Settings and Design: A retrospective study with CBCT examinations obtained from a database of a dental imaging center. Materials and Methods: A number of 174 adults' CBCT examinations of both genders were evaluated on the presence of calcifications along the course of the ICA and the number of MT as well as the PAI score. Statistical Analysis Used: The interobserver agreement was assessed by Cohen's kappa. The t-test for independent samples was used to compare the groups presented with or without calcifications. Furthermore, the Pearson's test was used to evaluate whether an association exists between variables that had a statistical difference. Results: The t-test showed a significant difference in the mean age (MA) and the number of MT between patients with and without presence of calcifications along the course of ICA, in both extra- and intracranial segments. The Pearson's correlation test showed a positive correlation between MA, MT, and both ExCICAs' presence and InCICAs' presence. Although the number of MT increases with age, this increment is high in the presence of ExCICA and even higher in the presence of InCICA. Conclusion: We support that not only patients' age but also the number of MT can be predictive for atherosclerosis "signs" presence.